Characterization of Total Family Risk and Family Type in a slum population in Northern Lima: Caracterización del riesgo familiar total y tipo de familia en pobladores de un asentamiento humano de un distrito de Lima Norte - Pérez Siguas, Rosa Eva (2017)
OBJECTIVES: This paper aims to determine the relationship between the characterization of Total Family Risk and Family Type in a slum population in northern Lima. MATERIALS AND METHODS: The method used was quantitative, descriptive and cross-sectional design. The population was 540 families consisted of 540 families. Data-collection was given between the second semester of 2014 and 2015 involving nursing students. Started an interview with the head of the family. The instrument used was Questionnaire RFT 5:33, which was adapted and validated to our reality. RESULTS: Globally, most families are within the vulnerable class (52.4%), vulnerable families are predominantly in the “social economic situation” and “child management” dimensions. In the family type 1, vulnerable families predominate in the dimensions “socio economic situation” and “child management, while in the family type 2 the vulnerable family is mainly in the dimensions” socio economic situation “and” health services and practices“. There is an association between total family risk and family type. CONCLUSIONS: It was concluded that, although in our study we found low frequency of highrisk families more than half of the families are vulnerable. Furthermore, it could identify a similar number of families with low risk, which justifies the continuation and strengthening of multidisciplinary and inter-institutional participation to eradicate, neutralize or reduce the risks in families.